Exploration of Legal Remedies Available to Fashion Designers in Ghana Through Global Industry Practices: A Review - Akosua Mawuse Amankwah; Richard Acquaye (Fashion and Textiles Review)
Although copyright law gives design protection to designers in most countries, the process appears to be unfriendly to fashion design.  The complex nature of its application coupled with the current fashion business model of constants introduction of new trends embedded in the theory of planned obsolescence makes it daunting and unappealing for designers to seek design protection. Literature reveals similarities of the copyright act in countries where it is operated including Ghana and the associated challenges. The recent call for industry transition to sustainable models positions fashion designers in Ghana to take advantage of their predominantly user-centred model for custom made garments to pursue design practices that encourage individualism to promote emotional attachments and product longevity for sustainability.